Elimination Methods for High-Frequency Harmonics on the DC Side of Modular Multilevel Converters from the Perspective of Valve Control - Qing Huai; Yirun Ji; Minxiang Yang; Ziyao Jie; Xi Yuan; Xiang Xu (Energies)
Modular multilevel converter (MMC)-based HVDC systems have become one promising way to integrate a large amount of renewable energy. However, the high-frequency harmonics problem could seriously affect the safety and stable operation level of MMC-HVDCs. Aiming at the high-frequency harmonics issues in MMC-HVDC projects, this study investigates the influence of the valve-level controller modulation control on the DC high-frequency harmonics of MMCs. Firstly, the mechanism of high-frequency DC voltage harmonics generated by carrier quantization errors is revealed. Research results demonstrate that carrier quantization errors alter the switching instants of upper and lower arm submodules, inducing wideband high-frequency DC voltage harmonics ranging from several kilohertz to hundreds of kilohertz. In addition, a discrete carrier compensation method based on amplitude symmetry is proposed to eliminate the impact of carrier quantization errors on DC voltage harmonics. Lastly, a carrier phase-shifted (CPS)-modulated MMC simulation model is built in Matlab/Simulink to validate the impact of carrier quantization errors on DC high-frequency harmonics and the effectiveness of the proposed discrete carrier compensation method.